Acute increases in countermovement jump height when combined with heavy back squats to form complex training sets - Pereira Sousa, A. (Journal of Australian Strength and Conditioning, 2018)
Complex training is the alternation of heavy and light resistances in order to achieve an acute improvement to the latter. This effect has been called postactivation potentiation. Exercises used for the heavy resistance "stimulation sets" are typically basic strength exercises such as back squats and bench presses, which are then combined with biomechanically similar explosive movements such as countermovement jumps or bench throws. Researchers have typically used heavy loads (=85% of one repetition maximum) for the stimulation set with equivocal results for upper and lower body. The purpose of this study was to determine if countermovement jump height was affected after performing sets of 2RM back squats. Eleven professional female volleyball players volunteered to perform four sets of 2RM back squats alternated with four sets of five countermovement jumps, with a 30-60 second rest period in between. The mean height of the countermovement jump sets, when compared to the baseline set, improved 4.13%, 5.67%, 4.73% and 2.75%, in the respective order. Statistically significant difference (p = 0.05) was found between the first (baseline) and third CMJ sets. No other set presented itself statistically different from the baseline set. These results demonstrate that complex training is effective at acutely enhancing power performance when the described protocols are applied.